2012
DOI: 10.7314/apjcp.2012.13.10.4855
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom: A Potent Anticancer Agent

Abstract: Since cancer is one of the leading causes of death worldwide, and there is an urgent need to find better treatment. In recent years remarkable progress has been made towards the understanding of proposed hallmarks of cancer development and treatment. Treatment modalities comprise radiation therapy, surgery, chemotherapy, immunotherapy and hormonal therapy. Currently, the use of chemotherapeutics remains the predominant option for clinical control. However, one of the major problems with successful cancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 37 publications
0
48
0
4
Order By: Relevance
“…Anticancer properties of snake venom proteins and their therapeutic potential have been reviewed recently by various authors. 9,35 In the present study, the cytotoxicity of M. l. obtusa venom against K562 cell line was observed and IC 50 values were calculated as 0.45 and 0.37 µg/mL by MTT and ATP assays, respectively. Although the results were similar, these two assays could give different results in certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer properties of snake venom proteins and their therapeutic potential have been reviewed recently by various authors. 9,35 In the present study, the cytotoxicity of M. l. obtusa venom against K562 cell line was observed and IC 50 values were calculated as 0.45 and 0.37 µg/mL by MTT and ATP assays, respectively. Although the results were similar, these two assays could give different results in certain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, immunotherapy has shown great promise for cancer treatment (Jain et al, 2012), however, resistance of cancer cells to immunotherapy remains a definite challenge. Studies have demonstrated that B7-H1 play a critical role in ovarian cancer immune evasion (Dong et al, 2002;Dong et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Natural venoms are useful biological resource, containing several pharmacologically active components that could be of potential therapeutic value. Many biotoxins have antitumor activity, some of them killing tumor cells directly, some inhibiting tumor angiogenesis and inhibiting tumor growth (Orsolic, 2012;Jain and Kumar, 2012). Here are several representative biological toxins that have antitumor applications.…”
Section: Biotoxins For Cancer Therapymentioning
confidence: 99%